2012
DOI: 10.1103/physrevb.86.045446
|View full text |Cite
|
Sign up to set email alerts
|

Progressive melting in confined one-dimensional C60chains

Abstract: C 60 fullerenes confined inside single-walled carbon nanotubes form an archetypal one-dimensional system. X-ray diffraction experiments, from room temperature to 1073 K, reveal an increasing melting phenomenon. Detailed analysis of the sawtooth peak characteristic of the fullerene organization allows the quantitative determination of fluctuations in intermolecular distances. The present results validate the predictions of one-dimensional statistical models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…The slope of the linear fit of these data allows extracting the quantity Nd 2 k B /2π 2 mv 2 , from which we can evaluate N 2700. This rather long chain size is perfectly compatible with the high filling ratio (97%) deduced from our x-ray scattering characterizations 21 and with the average size of the nanotubes estimated by TEM, i.e., between 1 and 5 μm. 23 Knowing v and N and injecting them into Eq.…”
Section: B "Low" Temperaturessupporting
confidence: 88%
See 4 more Smart Citations
“…The slope of the linear fit of these data allows extracting the quantity Nd 2 k B /2π 2 mv 2 , from which we can evaluate N 2700. This rather long chain size is perfectly compatible with the high filling ratio (97%) deduced from our x-ray scattering characterizations 21 and with the average size of the nanotubes estimated by TEM, i.e., between 1 and 5 μm. 23 Knowing v and N and injecting them into Eq.…”
Section: B "Low" Temperaturessupporting
confidence: 88%
“…7(b)]. In a previous study, 21 we also observed an important change in the linear thermal-expansion coefficient at this temperature. The transformation of the chain's physical nature is clearly revealed by the dynamics, the 1D order becoming unstable under the fluctuations of the lattice parameter.…”
Section: B "Low" Temperaturessupporting
confidence: 68%
See 3 more Smart Citations